Od wydarzenia katastrofy do kata/stroficznego czytania. Poezja Charles’a Baudelaire’a w relacji Jorge’a Semprúna L’écriture ou la vie - Kasper, Judith (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
This essay addresses the instable meaning of the term catastrophe over the course of history. The first part takes leave of the “the tiny fissures” in the continuous catastrophe noted by Walter Benjamin to develop a philology of the cata/strophe. This philology does not only register a given meaning (for instance, of the catastrophe), but intervenes actively as disruption. It insists on the strophe in the catastrophe, transforming catastrophe into cata/strophe that, in fatal situations, permits the poetic potential to become a dynamic force that can, at least on the linguistic level, open toward other dimensions without denying the catastrophe itself. The second part is dedicated to a reading of Jorge Semprún’s autobiographical novel L’écriture ou la vie from the perspective of this philological concept. It seeks to show how Semprún’s citing and reciting of Baudelaire’s strophes in the putrid atmosphere of the Buchenwald concentration camp literally produce, on the level of the signifiers, fresh air to breathe.